Kentucky's Best : Fifty Years of Great Recipes - Allison-Lewis, Linda (Book collections on Project MUSE., 2015)
To many, Kentucky means the greatest thoroughbreds in the world. To others, it is the home of the finest bourbon. But the obvious success of burgoo, Owensboro barbeque, and Harlan Sanders's Kentucky Fried Chicken carries the state's reputation for excellence to a wider audience. From the perfect mint julep to benedictine, from a classic hot brown to cheese chutney, Kentucky's Best captures the full range of the state's culinary delights. Linda Allison-Lewis combines traditional and gourmet dishes, offering recipes from all parts of the state and from beloved restaurants and inns. Start with a.